Freedom that is not Absolute: Ecological Ethics and Human-Nature Relationship in the Qur’an - Muhammad, Muhammad; Nurul Yaqin, M. Zubad; Reza Mahfud, Fakhris Khusnu; Alahmadi, Fahd Mohana S (Studia Ecologiae et Bioethicae, 2024)
This article presents an analysis of ecological ethics in the holy scripture of Islam through the intellectual interpretations of Muslim scholars. The primary focus is on discussing the limitations of human rights in utilizing ecology and the obligation to preserve it according to the perspective of the Qur'an. This discussion is particularly relevant for Indonesia, a country with a majority Muslim population, which is experiencing increasing ecological degradation. The article urges Muslims in Indonesia to refer back to the ecological principles within Islam, avoiding capitalist ideologies that contradict Islamic teachings. The research methodology used is literature analysis, drawing from the texts of the Qur'an and its exegesis, analyzed through thematic and descriptive-analytical interpretative approaches. Two main themes discussed are the limitations of human creativity towards ecology and the relationship between humans and nature. Research findings indicate that the Qur'an explicitly prohibits human behavior that can harm environmental sustainability. Although nature was created to meet human needs, humans are still forbidden to treat the environment carelessly. The Qur'an emphasizes the importance of maintaining ecological balance, forbids isrāf (wastefulness), and warns of punishment in the afterlife for those who damage the environment.